2015
DOI: 10.1186/s12969-015-0051-7
|View full text |Cite
|
Sign up to set email alerts
|

MRI thresholds for discrimination between normal and mild temporomandibular joint involvement in juvenile idiopathic arthritis

Abstract: BackgroundCurrently there is no consensus agreement on the degree of enhancement in normal temporomandibular joints (TMJ) in children, which makes it difficult for clinicians to distinguish between the presence/absence of mild synovitis. Quantitative measurements of synovial and condylar enhancement may be useful additions to current qualitative methods on early MRI diagnosis and follow up of TMJ involvement in JIA. The purpose of the study is to establish thresholds/tendencies for quantitative measures that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
1
15
0
3
Order By: Relevance
“…Our results are also supported by two other recent publications; in 46 children without TMJ disease von Kalle and colleagues [21]showed 73% (23, 123) mean increase in signal intensity in synovial tissue while Ma and co-workers [22] showed 66% (40, 92) mean increase in 24 children without rheumatologic disease.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are also supported by two other recent publications; in 46 children without TMJ disease von Kalle and colleagues [21]showed 73% (23, 123) mean increase in signal intensity in synovial tissue while Ma and co-workers [22] showed 66% (40, 92) mean increase in 24 children without rheumatologic disease.…”
Section: Discussionsupporting
confidence: 91%
“…The precision of assessing contrast enhancement of the TMJs in healthy children has been addressed in a few studies [21,22]. In a study of 100 contrast We found that the condylar inclination in the sagittal/oblique plane increased by age, and that 60% of children under the age of ten had straight condyles while the majority of those aged 17-18 years had marked anterior inclination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 While many prior MR imaging approaches have relied on subjective interpretation of synovial enhancement more recently, attempts have been made to assess the utility of quantitative analysis of TMJ synovial enhancements. [5][6][7][8] Peacock et al 6 defined a ratio of the TMJ synovial postgadolinium signal inten-sity normalized to the longus capitis muscle in control patients and found a 95% specificity threshold of 1.55. Resnick et al 8 found that the 1.55 threshold had a 91% sensitivity and 96% specificity for detecting synovitis in symptomatic JIA TMJs.…”
mentioning
confidence: 99%
“…However, measurement of synovial thickness in a small joint with 2 compartments and overlap of the disc and surrounding soft tissues is technically challenging, and the chronicity of disease implied by the presence of thickened synovium is unclear. Ma et al found that 20% of TMJs that had mild synovitis did not demonstrate hypertrophy of the synovium, and determined that synovial thickening was not a reliable marker for disease .…”
Section: Discussionmentioning
confidence: 99%